Integrating Islamic Sharia Principles into Educational Leadership: A Strategic Management Perspective - Farhan Zahiri; Abdurrohman Sahal (Pusat Riset dan Inovasi Nasional Mabadi Iqtishad Al Islami, 2025)
Teacher motivation, instructional effectiveness, professional learning, and retention continue to pose significant challenges in educational systems worldwide, often exacerbated by elevated levels of burnout and turnover. This study investigates the intersection between modern strategic management and Sharia-based leadership within Islamic educational institutions. Using a qualitative library research method, the paper analyzes recent scholarly literature to examine how Islamic ethics can be integrated into institutional governance. The findings suggest that modern management tools—such as strategic planning, SWOT analysis, and performance evaluations—can be effectively aligned with Islamic values when guided by principles such as shura (consultation), amanah (trust), and ‘adl (justice). However, a significant gap remains between theoretical ideals and actual administrative practices, often driven by bureaucratic and secular benchmarks. The study further identifies a lack of a comprehensive, operational Sharia-compliant leadership model that systematically combines strategic management theory with Islamic jurisprudence. Such a framework is essential for defining ethical leadership roles, participatory governance mechanisms, and accountability systems. Integrating Islamic ethics into leadership practices fosters stakeholder trust—among teachers, parents, and students—which in turn reinforces institutional legitimacy and supports long-term sustainability. The research emphasizes the need for Islamic educational institutions to move beyond symbolic adherence to Sharia and adopt integrated, ethically coherent leadership practices that address both moral and managerial imperatives.